Wieź fizyczna między małżonkami w prawie kanonicznym i polskim - Tomasz Rakoczy (Colloquia Theologica Ottoniana, 2016)
Physical bond between the spouses constitutes the essential binder of their relationship. Teaching of the Church shows the truth about marriage that includes the whole community of life, not only in terms of its duration, but also in the ability to cover all its dimensions. Polish law, emerging in the field of post-war period, has developed the concept of a physical relationship, consisting in maintaining relations between the spouses injury. Both legal systems (canon law and Polish) in an equally seriously, regarding the prerequisites, as well as the continuation of married life, look for impotence. Canon law determines the right to marry on the ability to take carnal intercourse. Also points to the consummation of the marriage institution, the lack of which can cause the request of one of the spouses of the solution node. The Polish law does not condition the ability to contracting marriage the ability to carnal intercourse. It sees, however, in the absence of cohabitation (whether arising from the departure of a spouse, or with impotence) the risk of relationship breakdown. However, it also requires in its case law and the doctrine not as absolute physical bond, because of its transience.